The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1068/a43167
|View full text |Cite
|
Sign up to set email alerts
|

ICT Intensity of Use and the Geography of Firms

Abstract: IntroductionThe diffusion of information and communication technologies (ICTs), because of their impact on growth and firms' productivity, has generated much literature. One important result of this literature is that ICT diffusion across agents and particularly across firms is uneven. Recent empirical studies in various fields show that, among the factors that explain such variations in firms' rates of ICT adoption, and which are related mainly to their internal characteristics and/or to the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Not surprisingly, there are differences between the marginal effect of and 4 on the extent to which manufacturers use the internet, as we had described in the section 4 that takes into account all firms in an industry, use manufacturer's market share as a weight, with smaller firm being given smaller weights and bigger firm being given bigger weights, while 4 is only consider the weighted average of the market shares of the top four-firms in an industry. However, our findings of industrial concentration agree with those of Galliano and Roux (2008) and Galliano et al (2011) who used French manufacturing industry data.…”
Section: The Regression Model With Selection Corrected For All Industrysupporting
confidence: 68%
“…Not surprisingly, there are differences between the marginal effect of and 4 on the extent to which manufacturers use the internet, as we had described in the section 4 that takes into account all firms in an industry, use manufacturer's market share as a weight, with smaller firm being given smaller weights and bigger firm being given bigger weights, while 4 is only consider the weighted average of the market shares of the top four-firms in an industry. However, our findings of industrial concentration agree with those of Galliano and Roux (2008) and Galliano et al (2011) who used French manufacturing industry data.…”
Section: The Regression Model With Selection Corrected For All Industrysupporting
confidence: 68%
“…Moreover, as AUDIA et al (2001) have demonstrated, the multi-unit location of a firm, per se, can foster learning between its units and facilitate organizational innovation. GALLIANO et al (2011) also demonstrate that this multi-location structure is conducive to technology adoption. Thus, if the spatial externalities can influence a firm's innovation capacity and particularly if it is recognized that the high level of innovation of a firm is generally associated with the location of the head offices in urban areas, the question becomes what impact the multiple locations of a firm have on its propensity to innovate.…”
Section: The Definition Of the Firmmentioning
confidence: 94%
“…However, certain studies have highlighted that the other units of a firm could play an important role in its performance and, for instance, in its propensity to adopt new technologies (BEARDSELL and HENDER- SON, 1999;GALLIANO et al, 2011). Thus, while the influence of head office location on the propensity of the firm to innovate has often been highlighted, taking into account the environment where the other units of the firm are located could help to evaluate better its innovation capacity in relation to the key role played by knowledge externalities.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, two variables have been studied: population density and the percentage of the urban population. The presence of an urban population has been considered to have a positive relationship due to the knowledge spillovers and network effects associated with ICT use by firms (Billon et al , 2009; Domenech et al , 2014; Galliano et al , 2011), and with patenting activity (Vinciguerra et al , 2011), although the evidence is less conclusive when considering ICT use by households (Billon et al , 2008; Prieger, 2013; Schleife, 2010; Stiakakis et al , 2010; Vicente and López, 2011). A similar situation is found in studies on the role played by population density.…”
Section: Conceptual Framework and Empirical Evidencementioning
confidence: 99%